IMPLEMENTASI PENDIDIKAN EKO-PROFETIK DI PONDOK PESANTREN - Muhamad Slamet Yahya; Ofi Afiatun Hindun Ulfah; Siswadi Siswadi (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Today, the existence of a negative stigma about Islamic boarding schools that are dirty and dirty, is increasingly dimmed along with the development of Islamic boarding schools that have an important awareness of the environment and the application of a healthy lifestyle. Islamic boarding schools are supposed to be one of the solutions so that human relations with nature can be well established, as well as the function of pesantren which plays a role in creating religious human beings based on the values of rahmatan lil alamin as agents of change, namely prophetic. Thus it is interesting to carry out an in-depth study to find out how the implementation of eco-prophetic education is for the healthy lifestyle of students. The research locus took place at the Darussalam Islamic Boarding School, Purwokerto. Based on the method, this study takes a qualitative paradigm using an ethnographic approach. As a result, the implementation of eco-prophetic education for the healthy lifestyle of students is considered quite good, with the findings of several pillars and forms of activity as follows: a) Eco-Transcendence (man and God), the forms of which include dhikr, habituation to healthy living, night prayers, and plant trees; b) Eco-Humanization (advice on goodness), its forms include protecting the environment, reminding each other, and competing in goodness; c) Eco-Liberation (preventing damage and evil), in the form of controlling scattered items, managing waste banks, and community cooperation.